Building Fiscal Capacity in Fragile States. (Policy Papers; Policy Paper ;, 2017)
The paper draws on recent country experience to describe the approach to designing and implementing fiscal reforms in fragile states (FS) taken in the IMF's technical assistance (TA). In doing so, it highlights how the TA that the IMF provides to FS differs from that of non-FS, describes the trends in and modalities of TA delivery, and draws on recent experiences to derive lessons for future work.